Importance of Cultural and Educational Activities for Openness and Affirmation of Archives in Society (Experiences of the Archive of Tuzla Canton) (Atlanti, 2016)
Cultural and educational activities are an important and indispensable segment of each archive. The same is manifested through various forms of action of exhibitions, cooperation with the media and educational institutions. We are talking about various facilities and projects that have multiple goals. One is presentation and affirmation of archival material as cultural heritage, as well as archives and archival activities. The second is the involvement of citizens, especially young people (students) in the project activities, thus raising awareness of the importance of the written cultural heritage. Opening the archives for citizens and society, through cultural and educational and other facilities at the time of global trends in the world, it certainly top priority. In this sense, the overall results are reflected in the level of affirmation, and (lack of) opennes of archives to society. Therefore, this paper aims to highlight the importance of cultural and educational activities, through the experience of the Archives of Tuzla Canton, for affirmation and greater openness of our Archives to professional, scientific, cultural, and the general public.
Keywords: cultural and educational projects; archives; openness of archives; affirmation of archives; Archive of Tuzla Canton